Findings encountered in percutaneous cholangiography in a case of post‐transplant recurrence of hepatic Langerhans cell histiocytosis with biliary involvement. (28th September 2020) - Faden, Iyad; Avitzur, Yaron; Abla, Oussama; Parra, Dimitri A.
Abstract: This case report describes a four‐year‐old boy who presented with the diagnosis of LCH with liver involvement. This required a living‐related liver transplant one year later. The primary disease recurred in the transplanted liver 6 months post‐transplant and led to progressive biliary dilatation. A percutaneous trans‐hepatic cholangiogram was performed five years after transplant, showing a pattern of multifocal biliary duct strictures mimicking the pattern of primary sclerosing cholangitis and a stenosis of the biliary‐enteric anastomosis. Despite management with an internal‐external biliary drain, the stenosis of the biliary‐enteric anastomosis evolved to an occlusion one year after drain removal. This was associated with progression of the changes in the biliary tree, this time associated with significant saccular dilatations secondary to the multiple areas of stenosis. Due to these findings and progressive deterioration of the function of the graft, the patient required re‐transplantation. This report illustrates the findings in imaging of the biliary tree secondary to the recurrence of LCH after liver transplantation, which may help to recognize this complication to physicians facing a similar clinical scenario.